PROPOSED RISK ASSESSMENT IN MICRO MANUFACTURING BUSINESS - Pérez Castañeda, Suly Sendy (2014)
Recognizing that micro companies are an essential part of national and international business community for his contribution to employment and wealth gene-ration, these are subject to risks that, if not properly managed, affect not only growth, but also threaten his residence, so it is essential to identify and measuring the level of risk exposure in these institutions; however, the existing methods are based on statistical data that these businesses do not generate.In this context, the paper presents a proposal of risk assessment in micro business from a qualitative pers-pective, based on the methodology of Enterprise Risk Management (ERM) in IEREM (Perez and Garcia Campos, 2013) instrument through a case study in Mexico metalworking manufacturing. The results show that ERM is a qualitative methodology easily applicable to these enterprises, which identifies chart and hierarchically in higher level of risk exposure.